2021
DOI: 10.18805/ijare.a-623
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Light Effects on Germination Behaviour of African Eggplant (Solanum aethiopicum L.) Seeds

Abstract: Background: A preliminary study of the African eggplant seeds obtained from farmers sources recorded a wide variation in percentage germination under ambient conditions (25±2°C). The germination percentage ranged from 0% to 25%, while fresh seeds ranged between 53% and 87%. As temperature and light are important factors of seed germination, the current study investigated the effect of temperature on the germination pattern and the influence of light interaction with temperature on seed germination of African e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is believed that the semi-domesticated Solanum distichum Schumach and Thonn is claimed to have contributed to the domestication of Solanum aethiopicum from the wild Solanum anguivi Lam [19]. Cultivars of Solanum aethiopicum can be categorized into flour groups: Shum, Kumba, Aculeatum, and Gilo Group [20,21,22]. The Kumba and Gilo cultivars are grown for their fruit, whilst Shum is grown for its leaves [23].…”
Section: Origin and Botanymentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the semi-domesticated Solanum distichum Schumach and Thonn is claimed to have contributed to the domestication of Solanum aethiopicum from the wild Solanum anguivi Lam [19]. Cultivars of Solanum aethiopicum can be categorized into flour groups: Shum, Kumba, Aculeatum, and Gilo Group [20,21,22]. The Kumba and Gilo cultivars are grown for their fruit, whilst Shum is grown for its leaves [23].…”
Section: Origin and Botanymentioning
confidence: 99%
“…When the fruits are in the commercial stage (physiologically immature), they might be white, green, or even purple in colour. Additionally, the fruit turns red or reddish-orange when it achieves full maturity, a colour change linked to a high carotene content [28,29,22]. The fruit is categorized as a berry since it has a firm firmness, a vibrant green calyx, and numerous tiny delicate seeds [30,31,14]; the kidney-shaped seeds have a diameter of 2-3.5 mm [26].…”
Section: Origin and Botanymentioning
confidence: 99%
“…Germination cannot be taken place below and above these extreme temperatures. Botey et al (2021) reported low germination of Solanum aethiopicum L. seeds at lower (15  C) and higher (35  C) temperatures. Gibberellins promote germination.…”
Section: Introductionmentioning
confidence: 96%
“…(A) Measurement of seed germination capacity: Seeds were subjected to germination tests in a germination incubator (Biobase: BJPX-B400II) at 30/20 °C with 8/16 hours of light and dark period for 14 days according to Botey et al, (2021a). The seed tests were uniform for all seed lots.…”
Section: Introductionmentioning
confidence: 99%